Kinetic investigations of the oxygen entry pathway of the hypoxia-inducible factor (HIF) prolyl hydroxylase 2 - Kearney, L (2015)
Human hypoxia inducible factor (HIF) is responsible for mediating the body’s response to low O2 availability. The levels and activity of HIF are regulated by four Fe(II)/2-oxoglutarate (2OG)-dependent oxygenases, prolyl-hydroxylase domains 1-3 (PHD 1-3) and factor-inhibiting HIF (FIH), collectively termed the HIF hydroxylases. The PHDs catalyse hydroxylation of specific prolyl residues in the N - and C - terminal oxygen-dependent degradation domains of HIF-α, targeting it for degradation by the proteasome. FIH catalyses hydroxylation of an asparaginyl residue in the C-terminal transactivation domain, preventing the interaction of HIF-α with the co-transcriptional activator p300. Under hypoxic conditions, the activity of the oxygen-dependent HIF hydroxylases is reduced, causing an increase in cellular HIF-α levels/activity and triggering the transcription of genes that enable the cellular and physiological hypoxic response. PHD2 is reported to be the key O2 sensor regulating the hypoxic response. It has also been reported to have a high Km(O2) value and a slow reaction with O2 in pre-steady state studies, kinetic features that are proposed to be related to its role as an O2-sensor. We are interested in the molecular features that enable this O2-sensing role, when other Fe(II)/2OG oxygenases react ∼100-fold more rapidly with O2. To investigate whether restricted O2 passage to the active site may be responsible for its unusual kinetics, our collaborators (C. Jorgensen and C. Domene, KCL) have conducted molecular dynamic studies to investigate the route of O2 entry to the PHD2 active site. These studies (unpublished) have indicated that O2 enters PHD2 via the interface between HIF substrate and a flexible, substrate-binding loop (the β2β3 loop) in PHD2. O2 is then proposed to reside in a stable 'E-cluster' in PHD2, before moving to the active site. This report describes work conducted to experimentally verify this predicted O2 entry pathway into PHD2, and to determine whether aspects of this entry pathway contribute to the slow kinetics of the reaction of PHD2 with O2. To validate the role of the β2β3 loop in the reaction of PHD2 with O2, kinetic studies of PHD2 loop variants were undertaken. These variants were previously developed by Flashman et al such that the β2β3 loop of PHD2 was altered to include the loop sequences of PHD1 and PHD3. These loop variants demonstrated reduced O2 sensitivity, and with the β2β3 loop of PHD3, a more rapid reaction with O2. These data suggest the β2β3 loop of PHD2 does indeed play an important role in O2 uptake. Experimental validation of the stable E-cluster was then undertaken. The site directed mutagenesis of methionine 299 in PHD2 to histidine did not yield different kinetics with respect to O2, suggesting either replacement of methionine 299 with histidine does not alter the O2 'stabilising' characteristics of the E-cluster or the E-cluster is not significant in O2 kinetics. Tryptophans 258 and 389 also form part of the E cluster. Laser-induced excitation of molecular O2 to O2* was used to attempt to modify and thus identify amino acid residues in regions where O2 was stably bound, i.e. the E-cluster. This approach was technically challenging, and results obtained were inconclusive. Further investigations using this method would require substantial optimisation. Stopped-flow tryptophan fluorescence quenching studies confirmed that these residues encounter a quenching species upon introduction of O2, supporting the hypothesis that they are present on the O2 uptake pathway. Interestingly, the rate of tryptophan fluorescence quenching of the PHD2variant.CODD.Fe(II).2OG complex by O2 correlates with the PHD2 WT rate of product turnover suggesting the quenching is correlated with product turnover. The results reported here imply that the rate limiting step with respect to PHD2 and O2 is prior to O2 reaching the E cluster. Overall the thesis supports the hypothesis that PHD2's β2β3 loop is involved in PHD2's O2–sensing capability. Experiments were unable to verify the existence of an E-cluster, including the finding that O2 encounters two tryptophans present along the proposed O2 uptake pathway in PHD2 at the same rate as PHD2 catalysis. The findings of this study suggest that the β2β3 loop of PHD2 may be a key molecular feature involved in O2 sensing by PHD2, a factor that could be taken into account when designing PHD2 inhibiting or activating therapies.